Differential Gene Expression Profiling of Mouse Uterine Luminal Epithelium During Periimplantation. (March 2014) - Xiao, Shuo; Diao, Honglu; Zhao, Fei; Li, Rong; He, Naya; Ye, Xiaoqin
Uterine luminal epithelium (LE) is critical for establishing uterine receptivity. Microarray analysis of gestation day 3.5 (D3.5, preimplantation) and D4.5 (postimplantation) LE from natural pregnant mice identified 382 upregulated and 245 downregulated genes in the D4.5 LE. Gene Ontology annotation grouped 186 upregulated and 103 downregulated genes into 22 and 15 enriched subcategories, respectively, in regulating DNA-dependent transcription, metabolism, cell morphology, ion transport, immune response, apoptosis, signal transduction, and so on. Signaling pathway analysis revealed 99 genes in 21 significantly changed signaling pathways, with 14 of these pathways involved in metabolism. In situ hybridization confirmed the temporal expression of 12 previously uncharacterized genes, including Atp6v0a4, Atp6v0d2, F3, Ggh, Tmprss11d, Tmprss13, Anpep, Fxyd4, Naip5, Npl, Nudt19, and Tpm1 in the periimplantation uterus. This study provides a comprehensive picture of the differentially expressed genes in the periimplantation LE to help understand the molecular mechanism of LE transformation upon establishment of uterine receptivity.